Wubeizi Ointment Suppresses Keloid Formation through Modulation of the mTOR Pathway - Tang, Zhiming (Biomed Res Int, 2020)
BACKGROUND: Wubeizi (Rhus chinensis Mill.) ointment has been shown as an effective treatment for keloids. However, the protective mechanisms of Wubeizi ointment are not fully understood. The mammalian target of rapamycin (mTOR) has been demonstrated to be associated with keloid pathogenesis. In the present study, we investigated if Wubeizi ointment suppressed keloid formation through the modulation of key molecules of the rapamycin (mTOR) pathway including phosphatase and tensin homolog (PTEN), phosphatidylinositol 3-kinase (PI3K), and protein kinase B (Akt). METHODS: A keloid mouse model and human keloid-derived fibroblasts were developed and treated with Galla chinensis. Immunohistochemistry, western blot, and reverse transcription-PCR were used to detect PI3K, PTEN, Akt, and mTOR in keloid tissues and keloid fibroblasts. The apoptosis and proliferation rate of keloid fibroblasts was, respectively, analyzed by flow cytometry according to the MTT assay. Statistical analysis was done using SPSS version 20.0. For two variable comparisons, a two independent samples t-test was used. For multiple variable comparisons, data were analyzed by one-way analysis of variance (ANOVA) followed by pairwise q-tests. RESULTS: Our in vivo and in vitro studies showed that Wubeizi ointment suppressed keloid formation through inhibition of fibroblast proliferation and promotion of fibroblast apoptosis. The underlying basis involves downregulation of p-Akt and p-mTOR as well as upregulation of PTEN. CONCLUSION: These findings may contribute to a better understanding of the mechanisms of Wubeizi ointment for treating keloids.